Application of experiential learning model to increase students motivation and learning outcomes - Balgis Swaneda Fortunela Fortunela; Hasan Subekti; Wahyu Budi Sabtiawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aimed to describe how the experiential learning model increases motivation and improves student learning outcomes in the knowledge domain. The research was a pre-experiment with a one-group pretest-posttest design. Junior high school (SMPN 1 Surabaya) students in the 7th grade were the subject. The research instruments are learning observation forms, pretest and posttest, and a motivation questionnaire. Data was collected using the learning method, student questionnaire, and pretest and posttest methods. The data analysis included examining learning implementation, test findings of enhanced motivation and learning outcomes using the Wilcoxon test and normalized gain analysis, and a checkup of motivation and student learning. The results showed that the learning model was implemented very well, with an average score of 93 percent at the first meeting and 96 percent at the second meeting. The students' motivation from the pretest was 59 percent with a strong category at the first meeting and then improved to 89 percent with an excellent classification at the second meeting. The second meeting had a higher percentage of 96 percent for student learning outcomes on knowing competency than the first meeting, with a measurement of 64 percent. In conclusion, the experiential learning preparatory in science learning can boost students' motivation and learning outcomes.